Neural Correlates of Posttraumatic Stress Disorder Symptoms, Trauma Exposure, and Postmigration Stress in Response to Fear Faces in Resettled Refugees. (July 2019) - Liddell, Belinda J.; Cheung, Jessica; Outhred, Tim; Das, Pritha; Malhi, Gin S.; Felmingham, Kim L.; Nickerson, Angela; Den, Miriam; Askovic, Mirjana; Coello, Mariano; Aroche, Jorge; Bryant, Richard A.
Refugees are exposed to multiple traumatic events and postmigration stressors, elevating risk for posttraumatic stress disorder (PTSD), but there is limited research into how these factors affect emotional neural systems. Here, resettled refugees in Australia ( N = 85) completed a functional magnetic resonance imaging scan while viewing fear and neutral faces. We examined the influence of PTSD symptoms, cumulative trauma, and recent postmigration stress on neural reactivity and regional coupling within the refugee sample. Cumulative trauma and postmigration stress but not PTSD symptoms correlated with fear-related brain activity and connectivity. Trauma exposure correlated with stronger activity but overall decreased connectivity in the bilateral posterior insula/rolandic operculum, postcentral gyrus, ventral anterior cingulate cortex, and posterior cingulate gyrus. Postmigration stress correlated with fusiform gyrus hyperactivity and increased connectivity in face-processing networks. Findings highlight the impact of past trauma and recent postmigration stress on fear-related neural responses within refugees over and above PTSD symptoms.